Combined control of PM and NOx emissions from small-scale combustions by electrostatic precipitation - Oleksandr Molchanov; Kamil Krpec; Jiří Horák; Lenka Kubonová; František Hopan; Jiří Ryšavý (Results in Engineering)
Electrostatic precipitators (ESPs) have demonstrated promise in reducing particulate matter (PM) emissions, but their potential for simultaneously reducing NOx in small-scale combustion systems remains largely unexplored. This study examines the potential of ESP with DC corona discharge of negative polarity to reduce both PM and NOx emissions from small-scale combustion. A chemical kinetic model is first developed to predict NOx removal in the ESP. The model accounts for the non-uniform electric field distribution and inhomogeneity of non-thermal plasma in chemical kinetic while remaining simple enough for practical engineering applications. This allows for the optimisation of ESP parameters during the initial design phase. Using this model, the ESP was developed and applied with different energisation regimes to control emissions from a 15 kW pellet combustion heating unit. The initial concentrations for PM and NOx were 48 mg/m3 and 305 mg/m3, respectively (0 °C, 101.3 kPa; at reference O2 = 10 %vol.). The efficiency of the ESP was both theoretically and experimentally determined for various operational regimes at voltages ranging from 6.8 to 11 kV. At 11 kV, the ESP demonstrated a PM removal efficiency of 99.99 % and a NOx removal efficiency of 38 %, achieving compliance with Ecodesign Directive limits. The model's predictions showed reasonable agreement with experimental data, with a slight miscalculation for both particle precipitation and NOx removal. These findings have significant implications for the design and operation of ESPs in small-scale biomass combustion systems, offering a foundation for optimising these devices for combined NOx and particulate matter control.